Sistem Informasi Forecasting Produksi Padi Menggunakan Metode Least Square - Fikri, Moh Ali; Ghozali, Ahmad Lubis; Darsih, Darsih (Jurnal Sistem Informasi Bisnis, 2025)
Agriculture has an important role in the commodity sector of the Indonesian people's economy. Indonesia is an agricultural country with extensive agricultural land. So it is truly ironic that Indonesia, as an agricultural country, has to import several basic food ingredients from abroad. Rice production data from year to year has decreased in Indonesia. If the decline in rice production continues in the future, Indonesia will not be able to cope with the increasing food needs of the people. More than 90% of the rice consumed by Indonesian people is self-produced. About 95% of this production is produced from rice fields. Indonesia's land area and territory are so large, a strategic step is needed that can overcome the problem of decreasing rice production. One step that can be taken is to mitigate rice production data by being able to read the data and process it into an appropriate source of information. One of the methods used is applying parameter estimation in regression analysis based on minimizing the sum of squares of the residuals created in the results of each individual equation, namely least squares. The data processed is rice harvest area, production and productivity by province in 2018-2020 and 2019-2023. The creation of the information system uses the PHP programming language version 8.2.4 which runs on the Apache 2.0 web server and the php-ml library. The research resulted in a forecast for rice production in 2024 of 52,676,827 tons, in 2025 of 51,936,919 tons, and in 2026 of 51,197,011 tons. Forecasting accuracy using the least squares method is very good with a MAPE value of 1.93%.